Anti–Tumor Necrosis Factor Therapy Restores Peripheral Blood B-cell Subsets and CD40 Expression in Inflammatory Bowel Diseases. Issue 12 (December 2015) - Li, Zhe; Vermeire, Séverine; Bullens, Dominique; Ferrante, Marc; Van Steen, Kristel; Noman, Maja; Bossuyt, Xavier; Rutgeerts, Paul; Ceuppens, Jan L.; Van Assche, Gert
Abstract : Background: Anti–tumor necrosis factor (TNF) therapy has become a standard therapy for severe inflammatory bowel diseases (IBD), but its effect on B lymphocytes is largely unexplored. In this study we investigated peripheral blood B cells, B-cell subsets, and CD40 expression in patients with IBD before and during anti-TNF therapy with infliximab (IFX). Methods: Blood was taken from healthy controls (n = 52) and patients with active IBD before (n = 46) and/or during anti-TNF therapy (n = 55). B-cell markers were detected by immunofluorescent staining and FACS analysis. Patients were classified as responders or nonresponders to anti-TNF therapy. Results: We found a numerical deficiency of circulating CD19 + B cells, a lower activation state (CD40 expression) and lower proportions of CD5 + B cells and IgM + IgD + CD27 + preswitched memory cells among B cells in active patients with IBD before IFX therapy compared with healthy controls. IFX treatment increased CD19 + B-cell numbers as well as the proportions of named B-cell subsets in responders but not in nonresponders. IFX more effectively upregulated CD40 expression in responders than in nonresponders. Restoration of B cells correlated with the biological response to therapy (C-reactive protein). Trough serum levels of IFX correlated with the number of B cells during therapy. Conclusions: A lower number of circulating B cells, a low CD40 expression, and a decrease in the proportion of CD5 + and in the preswitched memory subset characterize active IBD. Restoration of these abnormalities correlates with the clinical response to anti-TNF therapy. The mechanism for this effect on B cells should be further explored. Abstract : Article first published online 16 September 2015.